The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.gaitpost.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A video based method to quantify posture of the head and trunk in sitting

Abstract: Maintenance of a vertically aligned posture of the head and trunk in sitting is a fundamental skill that demonstrates the presence of neuromotor control. Clinical assessments of posture are generally subjective. Studies have quantified posture using different technologies, but the application of such technologies in a clinical environment remains difficult. Video recordings, however, are easily used clinically and have potential for quantitative analysis of movement. This study used a video-based method to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 14 publications
(22 reference statements)
1
27
0
Order By: Relevance
“…In the present study, markers were required to identify a head segment and enable the calculation of head segmental angles. Although a fully automated objective tool should be markerless to avoid the limitations of missing markers when tracking on 2D videos [13], the results of the present study give confidence for future work towards a markerless system. The further development of a tool based on these principles, has the potential to complement clinical assessments currently used (in addition to SATCo) to support the therapeutic interventions in physiotherapy that will contribute to the evidence-based practice decision making.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, markers were required to identify a head segment and enable the calculation of head segmental angles. Although a fully automated objective tool should be markerless to avoid the limitations of missing markers when tracking on 2D videos [13], the results of the present study give confidence for future work towards a markerless system. The further development of a tool based on these principles, has the potential to complement clinical assessments currently used (in addition to SATCo) to support the therapeutic interventions in physiotherapy that will contribute to the evidence-based practice decision making.…”
Section: Discussionmentioning
confidence: 68%
“…To generate results comparable to the existing literature, segment angles were computed according to [7], [9]. Results for the relevant segments (head, neck, UT, MT, LT, UL, LL, pelvis) for our fully automated method recorded comparable performance, 6.4° (MAE), to the current benchmark semiautomated method, 3.8° (MAE) (table 1).…”
Section: B Segment Anglesmentioning
confidence: 76%
“…This same data set had been used in previous research to develop a semi-automated, objective method for quantifying postural control [7]. That previous method reported problems of tracking drift and feature dropout (loss of feature during tracking), due to 3D motion in the 2D image plane, as well as occlusion of point-features [7], [9]. The present study introduced deep learning methods to overcome these problems and provide a fully automatic approach, which predicts the point-features directly from single images (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A method for quantifying postural alignment in sitting has been developed that uses a video-based system [8]. The aim of the study reported here was to explore the potential for an automated method to establish use of the upper limb component of the CKC.…”
Section: Introductionmentioning
confidence: 99%